Portfolio Disclosures and Year-End Price Shifts. - Musto, David K (Journal of Finance, 1997)
Commercial paper sells at an extra discount if it matures in the next calendar year but Treasury bills do not. The discount is apparent in downward price shifts before the year-end, and upward price shifts at the turn of the year that are significantly correlated with the simultaneous returns to small stocks, and that cannot reflect tax-loss selling. Cross-sectional and time-series tests on prices, as well as flow of funds evidence on trades by institutional investors, indicate that both the debt and equity patterns reflect agency problems related to portfolio disclosures.